Risk profiles for mild cognitive impairment and progression to dementia are gender specific. Issue 9 (1st May 2008) - Artero, S; Ancelin, M-L; Portet, F; Dupuy, A; Berr, C; Dartigues, J-F; Tzourio, C; Rouaud, O; Poncet, M; Pasquier, F; Auriacombe, S; Touchon, J; et al.
Abstract : Objective: To examine risk factors for mild cognitive impairment (MCI) and progression to dementia in a prospective community-based study of subjects aged 65 years and over. Methods: 6892 participants who were over 65 and without dementia were recruited from a population-based cohort in three French cities. Cognitive performance, clinical diagnosis of dementia, and clinical and environmental risk factors were evaluated at baseline and 2-year and 4-year follow-ups. Results: 42% of the population were classified as having MCI at baseline. After adjustment for confounding with logistic regression models, men and women classified as having MCI were more likely to have depressive symptomatology and to be taking anticholinergic drugs. Men were also more likely to have a higher body mass index, diabetes and stroke, whereas women were more likely to have poor subjective health, to be disabled, to be socially isolated, and to suffer from insomnia. The principal adjusted risk factors for men for progression from MCI to dementia in descending order were ApoE4 allele (OR = 3.2, 95% CI 1.7 to 5.7), stroke (OR = 2.8, 95% CI 1.2 to 6.9), low level of education (OR = 2.3, 95% CI 1.3 to 4.1), loss of Instrumental Activities of Daily Living (IADL) (OR = 2.2, 95% CI 1.1 to 4.5) and age (OR = 1.2, 95% CI 1.1 to 1.2). In women, progression is best predicted by IADL loss (OR = 3.5, 95% CI 2.1 to 5.9), ApoE4 allele (OR = 2.3, 95% CI 1.4 to 4.0), low level of education (OR = 2.2, 95% CI 1.3 to 3.6), subclinical depression (OR = 2.0, 95% CI 1.1 to 3.6), use of anticholinergic drugs (OR = 1.8, 95% CI 1.0 to 3.0) and age (OR = 1.1, 95% CI 1.1 to 1.2). Conclusions: Men and women have different risk profiles for both MCI and progression to dementia. Intervention programmes should focus principally on risk of stroke in men and depressive symptomatology and use of anticholinergic medication in women.